(untitled) (Swiss Medical Weekly, 2022)
AIM OF THE STUDY: To analyse hospital incidence and in-hospital mortality of patients treated for abdominal aortic aneurysms in Switzerland. METHODS: Secondary data analysis of case-related hospital discharge data of the Swiss Federal Statistical Office for the years 2009–2018. Patients who were hospitalised and surgically treated for nonruptured abdominal aortic aneurysms or hospitalised and treated for ruptured abdominal aortic aneurysms were included in the analysis. Standardised annual incidences rates were calculated using the European standard population 2013. In-hospital all-cause mortality rates were calculated as raw values and standardised for age, sex, and the van Walraven comorbidity score. RESULTS: A total of 10,728 cases were included in this study, of which 87.1% were male. Overall, 22.7% of the patients presented with a ruptured abdominal aortic aneurysm; 46% of these cases were surgically treated whereas 54% received conservative therapy. The age-standardised cumulative hospital incidences for treatment of nonruptured abdominal aortic aneurysms were 2.6 (95% confidence interval 2.5–2.8) and 19.7 (19.2–20.1) per 100,000 for women and men, respectively; for ruptured aneurysms it was 0.4 (0.3–2.4) per 100,000 in women, and 2.7 (2.6–2.9) in men. The annual incidence rates were stable in the decade observed. The adjusted mortality rates for treatment of nonruptured aneurysms decreased from 5.5% (2.6–11.2%) in 2009 to 1.4% (0.5–3.6%) in 2018 in women, and from 2.4% (1.3–4.5%) in 2009 to 0.6% (0.2–1.5%) in 2018 in men. The adjusted mortality rates for treatment of ruptured abdominal aortic aneurysms remained high without relevant improvements for either sex over time: for women 32.4% (24.1–42.1%), for men 19.7% (16.8–22.8%). CONCLUSIONS: The hospital incidence rates for nonruptured and ruptured abdominal aortic aneurysms remained unchanged in the decade observed. Compared with Germany, there was no evidence for a decrease in the annual incidence rates for ruptured abdominal aortic aneurysms in Switzerland. Mortality rates in the elective setting were low and decreased in the last decade but remained high in patients treated for ruptured aneurysms. Efforts to reduce the incidence of ruptured abdominal aortic aneurysms are needed to reduce aneurysm-related mortality in Switzerland.